FORMULASI TEH CAMELIA-MURBEI DENGAN BUBUK JAHE (Zingiber officinale) DAN ASAM JAWA (Tamarindus indica, L.) SEBAGAI MINUMAN KESEHATAN UNTUK MENINGKATKAN RESPON IMUN TIKUS - Sri Darningsih; Clara Meliyanti Kusharto; Sri Anna Marliyati; Dadan Rohdiana (Food and Nutrition Society of Indonesia, 2008)
The Camelia-mulberry tea has a big potential to becomes a healthy beverage according to its bioactive components, and added by red ginger powder and tamarind. Those ingredients may increase immunity againts various diseases. The aims of this study was to develop formula of a healthy beverage contained of two varieties of leaves (camelia and mulberry), with Ginger (Zingiber officinale) and Tamarind (Tamarindus indica, L.) This main research used mice strain Spraque Dawley, 1.5-2 month old with weight 75–105 gram. The instruments used in this study were tea maker, organoleptic test and ELISA test. The experimental design used factorial complete random design with 5 groups, where on each group consists of 5 mouse, with two selected variables of the best camelia-mulberry tea, i.e., multikaulis enzymatic oxidation + Gambung 7 enzimatic non-oxidation; bulk tea (Tea A) with difference time observation ( 0, 2 and 4 weeks). The given dosage was 1 ml/100 gram mice weight, with different concentration of camelia-mulberry tea i.e. 3, 6, 9, and 12 gram/ml. The statistical analysis of variance (ANOVA) shows that a significant different exist for the time observation of a mice serum IgG (p<0.05). Followed by Tukey test, which shows that a significant differences exist on IgG average at the beginning and after the 2nd weeks of treatment, and the 2nd weeks vs 4th weeks treatment.